Mesenchymal Stem Cells Improve Glycometabolism and Liver Regeneration in the Treatment of Post-hepatectomy Liver Failure - Ding, Hao-ran; Wang, Jing-lin; Tang, Zhen-ting; Wang, Yue; Zhou, Guang; Liu, Yang; Ren, Hao-zhen; Shi, Xiao-lei (Frontiers in Physiology, 2019)
Abstract Background: The mortality rate of acute liver failure after partial hepatectomy (PHLF) is very high, and the only effective treatment is liver transplantation. Cell transplantation is a potential treatment for acute or chronic diseases of the liver. Mesenchymal stem cells (MSCs) have been proved to have immunomodulatory functions in previous studies. In the present study, we showed that MSCs promoted glycogen synthesis and liver regeneration after 90% hepatectomy in rats. Our aim was to determine the efficacy and mechanism of MSCs transplantation in the treatment of acute liver failure after 90% hepatectomy. Methods: MSCs were isolated from Sprague-Dawley rats and cultured using a standardized protocol. The MSCs were transplanted to treat acute liver failure induced by 90% hepatectomy. Alanine transaminase (ALT), aspartate aminotransferase (AST), international normalized ratio (INR), serum ammonia, liver weight to body weight ratio, blood glucose, and histology were subsequently determined. To further study the mechanism of MSCs transplantation for acute liver failure after partial hepatectomy, we assessed the changes in the AKT/glycogen synthase kinase-3 (GSK-3β)/β-catenin pathway, and A-674563, an AKT inhibitor, was used to validate the findings. SPSS version 19.0 was used for statistical analysis, and the independent-samples t test was carried out to analyze the collected data. Results: MSCs transplantation lightened the liver injury in acute liver failure induced by 90% hepatectomy. MSCs transplantation improved the glucose metabolism in PHLF model. AKT/GSK-3β/β-catenin pathway was affected to promote cell proliferation and growth in the liver after MSCs transplantation. Conclusion: MSCs transplantation alleviates acute liver failure after 90% hepatectomy by influencing the AKT/GSK-3β/β-catenin pathway.